Ateleia glazioveana and Ocimum basilicum: plants with potential larvicidal and repellent against Aedes aegypti (Diptera, Culicidae) (Research, Society and Development, 2021)
The Aedes aegypti is the main vector of the transmission of diseases such as dengue, yellow fever, Chikungunya, and Zika. The agents used for the control of mosquito involve the use of synthetic compounds, which may cause toxicity and contamination environmental. Aiming to test the effectiveness of natural products, the aim of this study was to evaluate the larvicidal and repellent activity of extracts of Ateleia glazioveana Baill. (timbó) and essential oil of Ocimum basilicum L. (manjericão), against A. aegypti. The activities of hydroalcoholic (HEA) and dichloromethane (DEA) extracts from A. glazioveana against A. aegypti larvae were assessed after exposure for 24, 48, and 72 h, using water and Bacillus thuringiensis israelensis as negative and positive controls, respectively. For repellent evaluation, we investigated the sting attempts of A. aegypti in response to the application of HEA- and DEA-based body creams (5%), as well as an alcoholic spray based on the essential oil from O. basilicum. The repellency of these preparations was compared with negative (vehicle) and positive (DEET) controls. Although HEA showed no apparent larvicidal activity, DEA at concentrations of 150 to 500 mg/ml showed high larvicidal potential after 24 h, compared to the negative control group (p < 0.001). Moreover, the DEA-based cream and the alcoholic spray of O. basilicum based essential oil showed higher repellency compared with the vehicle (84.5% and 70.5%, respectively). Accordingly, it is possible to infer that extracts and preparations of A. glazioveana and O. basilicum exhibit larvicidal and repellent activity against A. aegypti.